Evaluación del tratamiento de agua de consumo humano del barrio Zumbalica, ubicado en el cantón Latacunga provincia de Cotopaxi - Chaluisa Umajinga, Dennis Andres (2024)
The research "Evaluation of Human Consumption Water Treatment in Zumbalica Neighborhood, located in Latacunga Canton, Cotopaxi Province" revealed a concerning presence of arsenic in the water from capture point 5, which exceeds the permissible limits set by the regulations Book VI, Annex 1 of the TULSMA. Consequently, various activities were carried out within the framework of this project, which included the planning of sampling, the definition of strategic monitoring points, on-site analysis of water conditions, as well as the collection, preservation, and transportation of relevant samples.